Comparative Analysis of Agility Levels Based on Gender in Children Aged 10-12 Years: A Cross-Sectional Study - Saputri, Triasti Bintang; Yulianti, Atika; Rahmawati, Nurul Aini (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/mifi.2024.v12.i03.p11, 2024)
Introduction : Gross motor skills are related to children's proficiency in various movements and are often used in sports activities. One aspect of gross motor development is agility. Mastery of physical skills in children aged 10-12 years provides a source of enjoyment and achievement, supporting play and other activities. Boys and girls differ both physically and morphologically. Agility impacts the optimization of children's motor skills in solving problems, participating in sports activities, fitness, coordination, and precision of movements. It also influences their concentration levels and academic performance in school. Methods : This study employed an observational analytical method with a cross-sectional design using purposive sampling. The research was conducted at SD Muhammadiyah 08 Dau, with a total sample size of 116 children. The Hexagon Agility Test was used as the instrument for this study. Results : The one-way ANOVA test showed no significant difference in agility based on age (p=0.24). However, the Mann-Whitney test results indicated a significant difference in agility levels based on gender (p=0.02). Conclusion : The study found a difference in agility levels among children aged 10-12 years based on gender. However, there was no difference in agility between the ages of 10, 11, and 12.   Keywords : 10-12 years, gender, agility, motor skills